PENGARUH PERMAINAN SAINS TERHADAP KEMAMPUAN BERPIKIR KRITIS ANAK KELOMPOK B DI TK NEGERI PEMBINA 2 PALEMBANG - Dian Novita Sari; Sri Sumarni; syafdaningsih syafar (Tumbuh Kembang: Kajian Teori dan Pembelajaran PAUD, 2017)
This study aims to see the influence of science game on the critical thinking ability of children in TK Negeri Pembina 2 Palembang, which includes 5 indicators: (1) not easily accept the opinions of others, (2) observe, (3) analyze, (4) make hypothesis , and (5) conclude. The type of research used is Pre Experiment with One Shoot Case Study design and use purposive sampling sampling technique with consideration of critical thinking ability that still low in class B1. The sample consisted of 20 children consisting of 16 boys and 4 girls. Data collection uses an observation sheet that is displayed in the form of a test score and converted to a value. Treatment conducted as many as 4 meetings. Each meeting is done by observation, then the data is processed by calculating the average of the critical thinking ability of the child. From result of analysis of t test data obtained tcount = 5,22 dan ttable = 1,73 with ?=0,05 and dk (19) tcount ? ttable. Can be seen from every meeting, the dominant indicator appears that is not easy to accept the opinions of others, it is seen from the behavior of children can answer their own questions given and able to provide an explanation and an indicator that does not appear that is making a hypothesis, the child can not distinguish between cause and The consequences that occur during the game of science. There are 11 children (55%) who are Growing Very Good, 6 children (30%) are Expanding According to Hope and 3 children (15%) Start Developing. So it can be concluded there is a significant influence of science games on the critical thinking ability of children.